2019
DOI: 10.22630/eiogz.2019.125.5
|View full text |Cite
|
Sign up to set email alerts
|

Cena a gotowość do zapłaty za określone produkty ekologiczne na przykładzie mieszkańców województwa lubuskiego

Abstract: The development of the organic food market has resulted from, among others, an increasing consumer awareness of healthy eating, caring for their loved ones, as well as the spread of information on exceedances regarding the level of pesticides in food, standards of dioxins in meat and many other toxic chemicals. Noteworthy is also the increasing availability of organic food. An increasing number of stores have in their range of products food from organic farming, which in effect affects the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As indicated by Bryła’s (2016) research, the critical barriers to the development of the organic food market in Poland were the high price, insufficient consumer awareness, low availability of organic products, short shelf life and low visibility in the shop [ 43 ]. The main barriers to organic food consumption, i.e., price and availability, have not changed and are the same as in many studies [ 26 , 27 , 30 , 45 , 46 , 47 ]. The problem with the availability of organic food has, until recently, particularly concerned organic meat, cold meats, honey and products thereof, fish and seafood and wine [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As indicated by Bryła’s (2016) research, the critical barriers to the development of the organic food market in Poland were the high price, insufficient consumer awareness, low availability of organic products, short shelf life and low visibility in the shop [ 43 ]. The main barriers to organic food consumption, i.e., price and availability, have not changed and are the same as in many studies [ 26 , 27 , 30 , 45 , 46 , 47 ]. The problem with the availability of organic food has, until recently, particularly concerned organic meat, cold meats, honey and products thereof, fish and seafood and wine [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 79%
“…The majority of respondents declared that they were able to pay about 20% more for an organic product than for a conventional one, and 13% indicated that they were not able to pay extra at all ( Figure 2 ). This shows an increase compared to the study by Kułyk and Michałowska (2019), where a price that is higher by around 5–10% was accepted, and as many as 38% were not able to pay more for an organic product [ 45 ]. A trend was observed that willingness to pay (WTP) a higher price for organic products increases with median consumption, but group 4 declaring a willingness to pay more than 30% of the price does not confirm this trend.…”
Section: Discussionmentioning
confidence: 83%
“…Also, the study by Kułyk and Michalowska (2019), already mentioned in the Introduction, showed that an acceptable price difference is in the range of 5-10% [47]. Bryła (2018) examined the determinants of Poles' willingness to pay a higher price for organic food compared to conventional products but without going into specific product groups [59].…”
Section: Discussionmentioning
confidence: 99%
“…These results can be used to target different age groups of consumers. Figure 7 shows that young respondents (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) most prefer a variety of apple products and the middle-aged (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59) and the oldest (60+) the least. All of them most prefer juices, and the young almost equally prefer smoothies and smooth mousses.…”
Section: Purchasing Behaviour and Preferences Of Consumers In The Stu...mentioning
confidence: 99%
“…Thus, in addition to the important issue discussed in this article (meeting human nutritional needs), equally important is the potential increase in consumption expenditure on food. However, various studies show that some conscious consumers are willing to incur higher costs for the purchase of sustainable products, e.g., domestic, health-friendly and environmentally friendly [49][50][51][52][53].…”
Section: Contribution To Further Research and Analysismentioning
confidence: 99%